Analisis Perbedaan Kinerja Keuangan PT Darya-Varia Laboratoria Tbk Sebelum dan Saat Covid-19 - Zetha Hayuning Pramesti; Tri Utomo Prasetyo (Sekolah Tinggi Ilmu Manajemen YKPN Yogyakarta, 2022)
This study aims to analyze the financial performance of PT Darya-Varia Laboratoria Tbk before and during Covid-19 through liquidity ratio, solvency ratio, profitability ratio and activity ratio. The Independent Sample T-Test is used for debt to total asset, debt to total equity, return on asset, total asset turnover and fixed asset turnover. The Mann Whitney U Test is used for current ratio, quick ratio and net profit margin. The results of this study are that there are no significant differences in the current ratio, quick ratio, debt to total assets, net profit margin, return on assets, total asset turnover and fixed asset turnover before and during Covid-19. Meanwhile, there are significant differences in debt to total equity before and during Covid-19.